1991
DOI: 10.1038/349796a0
|View full text |Cite
|
Sign up to set email alerts
|

ELAM-1 is an adhesion molecule for skin-homing T cells

Abstract: Endothelial cell leukocyte adhesion molecule-1 (ELAM-1) has been described as an inducible endothelial cell-adhesion molecule for neutrophils, and is believed to have a key role in the extravasation of these cells at sites of acute inflammation. Here we report that ELAM-1-transfected COS cells also bind a unique skin-associated subset of circulating memory T cells defined by the expression of the cutaneous lymphocyte-associated antigen. T cells expressing this antigen bind at least as well as neutrophils to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
356
0
6

Year Published

1991
1991
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 779 publications
(373 citation statements)
references
References 21 publications
11
356
0
6
Order By: Relevance
“…In support of this idea, memory T cells expressing an E-selectin ligand, designated cutaneous lymphocyte Ag-1 (CLA-1), are enriched within inflamed dermis compared with peripheral blood. It has been proposed that CLA-1 ϩ memory T cells use persistent E-selectin on dermal EC as an address signal for skin homing (4).…”
mentioning
confidence: 99%
“…In support of this idea, memory T cells expressing an E-selectin ligand, designated cutaneous lymphocyte Ag-1 (CLA-1), are enriched within inflamed dermis compared with peripheral blood. It has been proposed that CLA-1 ϩ memory T cells use persistent E-selectin on dermal EC as an address signal for skin homing (4).…”
mentioning
confidence: 99%
“…Parenthetically, IL-I and TNF-o can also be synthesized by thyroid epithelial cells [30,31 ]. E-selectin is not only involved in the adhesion of neutrophils and monocytes to EC in acute inflammation, but also plays an important role in the initial tethering of memory T cells to inflamed sites, as has been reported in chronic inflammation of the skin [32]. as well as in rheumatoid arthritis [13].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Eselcctin binds to the glycosylated cutaneous lymphoid antigen (CLA, HECA-452 antigen) expressed by T and B eells [10], and P-selectin also recognizes the non-sialylated Lewis^ (Le^, CD15) [II]. E-and P-seleetins can interact not only with neutrophils and natural killer (NK) cells, but also with certain minor T cell subsets, chronically activated T cells, at those infilirating chronic inflammatory sites [12,13]. In addition, we have recently reported in HT the presence of sLe".…”
mentioning
confidence: 99%
“…These findings suggested that allergic response induced by IgE and mast cells causes preparation for infiltration of lymphocytes, eosinophils, and neutrophils into the bronchial mucosa. In other organs, e.g., intestine, skin, and lymph nodes, tissue-specific adhesion molecules, chemokines, and their receptors that recruit T cells have already been discovered (15)(16)(17)(18)(19). Despite these discoveries, it is not well known how T cells recirculate into the bronchial mucosa in allergic diseases such as asthma.…”
mentioning
confidence: 99%